2010
DOI: 10.1155/2011/636134
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Integrative Health Care Research: Randomized Control Trials, Clinical Controlled Trials, and Meta‐Analysis

Abstract: A systematic review was conducted to assess the level of evidence for integrative health care research. We searched PubMed, Allied and Complementary Medicine (AMED), BIOSIS Previews, EMBASE, the entire Cochrane Library, MANTIS, Social SciSearch, SciSearch Cited Ref Sci, PsychInfo, CINAHL, and NCCAM grantee publications listings, from database inception to May 2009, as well as searches of the “gray literature.” Available studies published in English language were included. Three independent reviewers rated each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
(46 reference statements)
0
35
0
Order By: Relevance
“…That is, the integration of conventional (allopathic) medicine and CAM, involving shared management of the patient, shared patient care, shared practice guidelines, and shared common values and goals to treat the well-being of the whole person' [40]. We will see if this definition becomes widely adopted [41,42].…”
Section: Trends In Terminologymentioning
confidence: 99%
“…That is, the integration of conventional (allopathic) medicine and CAM, involving shared management of the patient, shared patient care, shared practice guidelines, and shared common values and goals to treat the well-being of the whole person' [40]. We will see if this definition becomes widely adopted [41,42].…”
Section: Trends In Terminologymentioning
confidence: 99%
“…17 Although only a small number of studies have been published, biomedical dominance has also been observed in the IM setting. 3,9 There is a tendency for biomedical doctors to control patient care and use biomedical language as the main form of communication between practitioners. 18,19 Research confirms the significant impact biomedical practitioners' attitudes and knowledge of TCAM have on the style of IM practiced and the level of integration.…”
Section: Biomedical Dominancementioning
confidence: 99%
“…1 Professional bodies and researchers have proposed a range of definitions for and approaches to integrative medicine (IM); however, a final definition is likely to emerge and settle only as the practice of IM develops. [1][2][3][4][5][6][7] IM teams and health care models Given the diversity of descriptions of IM, it is not surprising that clinics claiming to offer IM also provide health care using different team arrangements and service models.…”
Section: Introductionmentioning
confidence: 99%
“…These IM definitions and dimensions reinforce the fact that IM does not aim to reject or replace either CAM or conventional therapies: it advocates combining both types of therapies when the combination is relevant to the individual's needs and is safe and evidence-based (Kotsirilos et al 2010). Khorsan et al (2011) undertook a systematic review of IM and identified an extensive and increasing body of literature on the subject that can be used to support practice. However, because IM is an emerging field in many countries, there may be less evidence for IM than for individual CAM.…”
Section: Integrative Medicinementioning
confidence: 99%